Role of Cell Death in Cellular Processes During Odontogenesis - Abramyan, John; Geetha-Loganathan, Poongodi; Šulcová, Marie; Buchtová, Marcela (Frontiers in Cell and Developmental Biology, 2021)
The development of a tooth germ in a precise size, shape, and position in the jaw, involves meticulous regulation of cell proliferation and cell death. Apoptosis, as the most common type of programmed cell death during embryonic development, plays a number of key roles during odontogenesis, ranging from the budding of the oral epithelium during tooth initiation, to later tooth germ morphogenesis and removal of enamel knot signaling center. Here, we summarize recent knowledge about the distribution and function of apoptotic cells during odontogenesis in several vertebrate lineages, with a special focus on amniotes (mammals and reptiles). We discuss the regulatory roles that apoptosis plays on various cellular processes during odontogenesis. We also review apoptosis-associated molecular signaling during tooth development, including its relationship with the autophagic pathway. Lastly, we cover apoptotic pathway disruption, and alterations in apoptotic cell distribution in transgenic mouse models. These studies foster a deeper understanding how apoptotic cells affect cellular processes during normal odontogenesis, and how they contribute to dental disorders, which could lead to new avenues of treatment in the future.